FRI0566 THE FLARE-RA QUESTIONNAIRE CAN IDENTIFY OMERACT FLARES IN PATIENTS WITH RHEUMATOID ARTHRITIS INCLUDED IN THE TAPERA TRIAL. (2nd June 2020) - Bertrand, D.; Stouten, V.; Pazmino, S.; De Cock, D.; Moeyersoons, A.; Westhovens, R.; Joly, J.; Verschueren, P.
Abstract : Background: The Flare assessment in rheumatoid arthritis (FLARE-RA) questionnaire has been developed to identify flares in patients with rheumatoid arthritis (RA). The first version was published by Berthelot et al. (2012) and consisted of 13 questions on a Likert-scale of 1-6 ranging from 'completely untrue' to 'completely true'. When the FLARE-RA questionnaire was validated by Fautrel et al., 2 questions were removed, and it was rescaled to 0–10. The questionnaires' usefulness has been tested in few studies. Further external validation in a well-defined cohort of patients with RA is needed. Objectives: To externally validate the FLARE-RA questionnaire and determine cut-offs for identifying a flare in an established RA population in which biologicals are tapered. Methods: Patients who were in remission according to the DAS28CRP or ESR (≥6 months) and treated with etanercept 50 mg weekly (≥1 year), were enrolled between 2012 – 2014 in the pragmatic 1-year open-label randomised controlled TapERA (Tapering Etanercept in RA) trial. Patients were randomised to continue etanercept 50 mg weekly or taper to 50 mg every other week. The FLARE-RA questionnaire (version of 2012) was completed every 3 months. Outcomes were based on 3 versions of the questionnaire (13 questions (13q), 11 questions (11q) and 11 questions rescaled (r11q)). Per time point, the average of the answers was calculated to obtain a total score of the FLARE-RA questionnaire. The total scores were compared between patients in remission (DAS28CRP <2.6), low (DAS28CRP ≥2.6 - ≤3.2), moderate (DAS28CRP >3.2 - ≤5.1) and high disease activity (DAS28CRP >5.1) using the Kruskal-Wallis test and between patients with and without a flare according to the OMERACT definition (increase in DAS28 >1.2 compared to baseline or increase in DAS28 >0.6 and current DAS28 ≥3.2) using the Mann-Whitney U test. The total FLARE-RA scores of the different time points were combined to determine the receiver operating characteristics (ROC) curves, the corresponding cut-off values and the area under the curve (AUC) for identifying an OMERACT flare. An AUC of <0.5, between 0.5 and 0.7 and >0.7 stands for having no, moderate and a good predictive value, respectively. Results: FLARE-RA questionnaires of 66 patients (68% female, mean ± standard deviation (SD) age of 55 ± 11 years) were collected. The FLARE-RA score (13q) did increase when disease activity increased at month (M) 3 and M12 (p<0.01) (table 1 ). Patients presenting with an OMERACT flare had a statistically significantly higher total FLARE-RA score (13q) compared to patients without a flare, except at M12 (M3 and M6: p<0.05, M9: p<0.01). The AUC - ROC curve of the FLARE-RA questionnaire (13q) for identifying an OMERACT flare was 0.736 and the cut-off value was 2.3 (1-6 scale). The AUC - ROC curve was the same for the 11q and r11q version, namely 0.727. The cut-off values were 2.4 (1-6 scale) and 2.7 (0-10 scale), respectively (figure 1 ). Conclusion: The FLARE-RA scores seem to reliably discern between patients with and without an OMERACT flare. A cut-off of 2.7 on the current questionnaire (r11q) had the optimal sensitivity and specificity to identify an OMERACT flare. Disclosure of Interests: Delphine Bertrand: None declared, Veerle Stouten: None declared, Sofia Pazmino: None declared, Diederik De Cock: None declared, Anneleen Moeyersoons: None declared, Rene Westhovens Grant/research support from: Celltrion Inc, Galapagos, Gilead, Consultant of: Celltrion Inc, Galapagos, Gilead, Speakers bureau: Celltrion Inc, Galapagos, Gilead, Johan Joly: None declared, Patrick Verschueren Grant/research support from: Pfizer unrestricted chair of early RA research, Speakers bureau: various companies